Comparing surgeon outcomes in endoscopic sinus surgery for chronic rhinosinusitis. (14th June 2016) - Smith, Timothy L.; Mace, Jess C.; Rudmik, Luke; Schlosser, Rodney J.; Hwang, Peter H.; Alt, Jeremiah A.; Soler, Zachary M.
Abstract : Objectives/Hypothesis: The objective of this investigation was to evaluate endoscopic sinus surgery (ESS) outcomes for chronic rhinosinusitis (CRS) between medical centers to determine if differences in quality‐of‐life outcomes were detectable. In addition, we sought to identify significant, independent cofactors toward the development of an ESS‐specific risk‐adjustment model so that ESS outcomes may be appropriately compared between institutions and healthcare providers. Study Design: Prospective, multicenter, observational cohort. Methods: Study participants electing ESS for CRS were enrolled and randomly selected in equal numbers from three academic clinical practices in North America between April 2011 and May 2015. The magnitude of average 6‐month postoperative improvement in patient‐related outcome measures (PROMs) was compared between enrollment sites using multivariate linear regression modeling. Results: A total of 228 participants met inclusion criteria and were included for final analyses (n = 76 per site). The prevalence of septal deviation/septoplasty and oral corticosteroid‐dependent conditions was significantly different between enrollment sites ( P ≤ 0.004). Each enrollment site generated significant within‐subject improvement across all PROMs after ESS ( P < 0.001); however, average unadjusted magnitudes of improvement were significantly different between sites for the primary outcome measure. After controlling for baseline PROMs, septal deviation, steroid‐dependent conditions, and medication use variables, enrollment site was no longer associated with significant outcome differences ( P = 0.535). Conclusion: Comparison of surgeon outcomes of ESS is feasible and must take into account a number of baseline patient characteristics. Further studies will be critical toward developing an ESS‐specific risk‐adjustment model and enabling a robust comparison of surgeon outcomes. Level of Evidence: 2c. Laryngoscope, 127:14–21, 2017